Kinetics Model and Optimization for Photocatalytic Degradation of Methylene Blue over Ag/TiO2 Catalyst - Kadem, Amna Jwad; Lau, Xian Jin; Pung, Swee Yong; Sreekantan, Srimala; Ramakrishnan, Sivakumar (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2025)
Titanium dioxide (TiO2) particles are widely used as photocatalysts due to their stability, low toxicity, and relatively low cost. However, their application is limited by a wide bandgap and a high recombination rate. This project investigated the photocatalytic performance of Ag/TiO2 catalyst, prepared by coupling Ag metal to TiO2 using the liquid impregnation method. The photocatalytic activity of different concentrations of Ag metal solutions and different pH levels of Ag/TiO2 catalyst under UV and visible light irradiation was observed. It was shown that Ag/TiO2 catalyst had the best photodegradation efficiency (83.82%) and the highest rate constant (0.03298 min-1) in 50 ppm Ag metal concentration and at pH 5 under UV light irradiation. The operating conditions were optimised by using the Design of Experiment (DOE) and Response Surface Methodology (RSM) to obtain optimum photodegradation efficiency (PE). The optimum parameters were 22.6263 ppm Ag metal solution and pH of 5, which were estimated to produce the highest photodegradation efficiency (84.0006 %) and rate constant (0.0321 min-1). The concentration of the methylene blue (MB) followed a first-order exponential decay and showed a decreasing trend from its initial concentration. In addition, the photocatalytic degradation rate of MB has been modelled successfully by Power Law kinetic model derived from the Langmuir-Hinshelwood framework. Numerical and analytical methods were implemented to solve the Langmuir-Hinshelwood equation, and both methods were very effective in agreement with the trend shown by the experimental data. In terms of photodegradation efficiency, the kinetic model has slightly over predicted the experimental model due to some minor experimental error, but the experimental data effectively complied with the theoretical micro kinetics investigations simulated using Power Law kinetic model. Copyright © 2025 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).